Measured haplotype analysis of the aldosterone synthase gene and heart size. - Mayosi, B; Keavney, B; Watkins, H; Farrall, M (2003)
Gene-association studies of heart size and the aldosterone synthase (CYP11B2) gene have produced inconsistent results, possibly because of limitations in the sample size and/or the number and location of the polymorphisms. An analysis of six polymorphisms spanning 6 kb of the CYP11B2 gene in Caucasian British families revealed a limited number of haplotypes because of strong linkage disequilibrium over this small region. The genotype and haplotype information was used in an association study involving 955 members of 229 families phenotyped for echocardiographic measures of heart size. In a mixed effects linear modelling analysis, the G5937C polymorphism was associated with cardiac wall thickness (P=0.02), and the intron conversion and A4550C polymorphisms were associated with left ventricular cavity size (P=0.02 and 0.002, respectively). Measured haplotype analyses confirmed the association of alleles at the intron conversion and G5937C polymorphisms with cardiac wall thickness (P=0.02), and alleles at the intron conversion polymorphism with left ventricular cavity size (P=0.04). The polymorphisms contributed to 2.0-3.4% of the variability in these traits. In summary, genetic polymorphisms at the CYP11B2 gene make a small contribution to quantitative variation in echocardiographic measures of heart size. These results point to the importance of analysing the full extent of genetic variation that captures the haplotype structure of a locus in gene association studies.